Diabetic Microangiopathy Is an Independent Predictor of Incident Diabetic Foot Ulcer - Tomita, Masuomi (J Diabetes Res, 2016)
Aim. To determine the diabetic foot ulcer incidence and examine its association with microangiopathy complications, including diabetic retinopathy (DR) and albuminuria (Alb), in type 2 diabetes patients. Methods. This was a retrospective cohort study of 1,305 patients with type 2 diabetes who were assigned to the following groups: Category 1, normoalbuminuria without DR (n = 712); Category 2, Alb without DR (n = 195); Category 3, normoalbuminuria with DR (n = 185); and Category 4, Alb with DR (n = 213). Cox proportional hazard models were used to compare the risks of developing diabetic foot ulcers across the categories. Results. During 14,249 person-years of follow-up, 50 subjects developed diabetic foot ulcers, with incidence rates of 1.6/1,000, 1.5/1,000, 3.4/1,000, and 12.5/1,000 person-years in Categories 1, 2, 3, and 4, respectively. After adjusting for the presence of diabetic neuropathy and macroangiopathy, the hazard ratios and 95% confidence intervals (CIs) for the risk of diabetic foot ulcer development were 0.66 (95% CI, 0.18–2.36), 1.72 (95% CI, 0.67–4.42), and 3.17 (95% CI, 1.52–6.61) in Categories 2, 3, and 4, respectively, compared with Category 1. Conclusion. The presence of DR and Alb significantly increases the risk of diabetic foot ulcer development.